Pod niebem tożsamości życia i śmierci… Jak rozmawiać z uczniami o doświadczeniach z czasów wojny - Jeziorkowska-Polakowska, Anna (Dydaktyka Polonistyczna, 2016)
The article, targeting Polish language secondary school teachers, relates to the way of interpreting the theme of II World War with literature students. The proposed work of Adolf RudnickiGinący Daniel reveals not just the broad historic perspective of those living in the capital duringthe Extermination but also creates a great possibility for numerous interpretations. Ginący Danielclearly conforms to the requirements of Polish language curriculum for the IV stage of education, inparticular the part relating to literary context of discussed works. The Rudnicki’s text gives opportunity to make reference to Pamiętnik z powstania warszawskiego by Miron Białoszewski, listedin the list of literary works for III stage of education. There is also a possibility to make an attemptto indicate collective locations of Jewish and Polish literature, citing Icchoka Lejba Pereca’s workMiędzy dwiema górami. Moreover, an autobiographical context can be applied to start a discussionabout Rudnicki’s literary works. Lastly, numerous biblical references, in the article narrowed downto Book of Daniel, are used to analyse and interpret Ginący Daniel in the way that students havea possibility to enjoy a real literary adventure.